1979
DOI: 10.1111/j.1399-0039.1979.tb00833.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA Antigens in a Scottish Psoriatic Population

Abstract: Sixty‐one patients in the Dundee area suffering from psoriasis were typed for HLA—A and HLA—B antigens. On the basis of the typing results, the patients were divided into three groups, and studied with respect to sex, age of onset and familial incidence of the disease. The frequency of HLA—A1 appeared to be increased and HLA—B7 decreased but HLA—B13 and HLA—B17 were highly significantly increased (P < 10−6 and P < 10−10 respectively) in the psoriatic group compared to 204 controls. Of particular interest was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

1981
1981
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 21 publications
0
17
0
1
Order By: Relevance
“…Eight of the 19 articles studied the association of HLA‐B*27 with PsV, and the results indicated that the association varied significantly by country. The OR was 3·49 in cases in China, and 1·77 in Germany, 1·19 in Finland, 1·00 in Japan, 0·95 in Scotland, 0·87 in Great Britain, 0·71 in Italy and 0·46 in India . All of the 12 articles concerning PsA reported a positive association between HLA‐B*27 and PsA, with ORs of 2·06–7·45 in Spanish subjects, and 5·80 in Germany, 5·53 in New Zealand, 4·90 in India, 3·51 in Great Britain, 3·03 in the Netherlands, 2·86 in Romania and 1·9 in Sweden .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight of the 19 articles studied the association of HLA‐B*27 with PsV, and the results indicated that the association varied significantly by country. The OR was 3·49 in cases in China, and 1·77 in Germany, 1·19 in Finland, 1·00 in Japan, 0·95 in Scotland, 0·87 in Great Britain, 0·71 in Italy and 0·46 in India . All of the 12 articles concerning PsA reported a positive association between HLA‐B*27 and PsA, with ORs of 2·06–7·45 in Spanish subjects, and 5·80 in Germany, 5·53 in New Zealand, 4·90 in India, 3·51 in Great Britain, 3·03 in the Netherlands, 2·86 in Romania and 1·9 in Sweden .…”
Section: Resultsmentioning
confidence: 99%
“…Table S3 (see Supporting Information) shows the results of quality assessment. Thirteen studies lacked a definition or diagnosis of psoriasis . Four studies did not report clearly how the patients were selected .…”
Section: Methodsmentioning
confidence: 99%
“…The first publications about the association of human leukocyte antigens (HLA) and psoriasis date from the 1970s, yet including population studies on Caucasian, 5–10 and non‐Caucasian patients with psoriasis vulgaris 11 . At that time, serological typing was the only method available and HLA‐B17, HLA‐B13 and HLA‐Cw6 were already considered to be associated with psoriasis vulgaris in Caucasian populations, mainly in the early‐onset type of the disease 12–15 . HLA class II antigens were also studied and an increased frequency of HLA‐DR7 was seen associated with psoriasis by that time 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Table presents the results of quality assessment of the included studies. Eleven articles did not provide the definition or diagnosis of psoriasis . Four articles did not specify the selection of patients .…”
Section: Resultsmentioning
confidence: 99%
“…Four articles did not specify the selection of patients . In seven articles, the selection criteria for the controls were not explained clearly, or data from blood or organ donors were used as control . Twenty‐two articles did not provide information about age, gender or race of subjects .…”
Section: Resultsmentioning
confidence: 99%